Extracellular vesicles as biomarkers and drug delivery systems for tumor - Xue Wang; Wenjing Chen; Wei Zeng; Kuanhan Feng; Yu Zheng; Ping Wang; Fucai Chen; Wen Zhang; Liuqing Di; Ruoning Wang (Acta Pharmaceutica Sinica B)
Extracellular vesicles (EVs) are crucial for facilitating intercellular communication, promoting cell migration, and orchestrating the immune response. Recently, EVs can diagnose and treat tumors. EVs can be measured as biomarkers to provide information about the type of disease and therapeutic efficacy. Furthermore, EVs with lower immunogenicity and better biocompatibility are natural carriers of chemicals and gene drugs. Herein, we review the molecular composition, biogenesis, and separation methods of EVs. We also highlight the important role of EVs from different origins as biomarkers and drug delivery systems in tumor therapy. Finally, we provide deep insights into how EVs play a role in reversing the immunosuppressive microenvironment.